YIELD OF VARIETAL MULBERRIES WITH DOUBLE OPERATION IN THE CONDITIONS OF THE KARSHI STEPPE - Рахмонбердиев В. К.; Хайдаралиев Ж. Р. (Journals Park Publishing, 2024)
The article discusses the results of a study of the leaf formation of various mulberry combinations during double use and it can be concluded that forage plantings in newly developed saline soils should be planted from varietal mulberries.
Keywords: variety, feeding, shoot, leaf, combination, vegetation, operation, leaf formation.